2018
DOI: 10.1108/ecam-07-2016-0166
|View full text |Cite
|
Sign up to set email alerts
|

Modeling of workers’ learning behavior in construction projects using agent-based approach

Abstract: Purpose-Learning as the way in which labor acquire new knowledge and skills has important strategic implications for the competitive advantage of an organization. The purpose of this paper is to present an agent-based modeling (ABM) approach to investigate the learning behavior of workers. The effect of interactions among different workers as well as the factors affecting the workers' learning behavior is assessed using the proposed ABM approach. Design/methodology/approach-For this purpose, the processes thro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 56 publications
0
4
0
Order By: Relevance
“…According to the theory of objective management, it is necessary to decompose the whole objective into the lowest level. From individual to department team, in order to form the bottom, control and guarantee the relationship between layers [8].…”
Section: ) Total Quality Controlmentioning
confidence: 99%
“…According to the theory of objective management, it is necessary to decompose the whole objective into the lowest level. From individual to department team, in order to form the bottom, control and guarantee the relationship between layers [8].…”
Section: ) Total Quality Controlmentioning
confidence: 99%
“…Son and Rojas (2011), Ahn and Lee (2015), Mahjoubpour et al (2018), Kedir et al (2020), Akcay and Arditi (2022) verified that the model can effectively improve worker behavior. Mahjoubpour et al (2018) simulated and analyzed the influence of factors such as interaction and characteristics among employees of construction workers' learning behavior and the change of employees' working ability in the process. The research findings showed that the model helps to coordinate the relationships between learning behavior and performance in projects.…”
Section: Coordination Of Multi-party Relationshipsmentioning
confidence: 79%
“…ABM is used to model and examine various situations, circumstances, and real-life phenomena. For example, ABM was successfully used to analyze the influences on employees' learning behavior [39], to mimic micro-level construction management procedures [40], and to examine how various incentive schemes affect safe behavior [41]. AMB has also been utilized in previous studies to simulate complex, adaptable, and decentralized emergent systems in the fields of social and environmental sciences and economics [42].…”
Section: Agent-based Modeling In Construction Researchmentioning
confidence: 99%